Pengembangan Minat Bakat Islami Anak Melalui Kegiatan Gebyar Muharram - Dahlan, Zaini; Wafi, Haikal; Andini, Maysarah; Desnita (Jurnal Dirosah Islamiyah, 2024)
The implementation of community service by PGMI UINSU students was carried out for 10 days, starting from July 24 to August 1. In community service activities, students carry out several planned community service programs. In the work program for this activity, students carry out activities to welcome the Islamic New Year. In welcoming this activity, students created a Muharram Festival activity, collaborating with mosque youth and the community in Dahlia Hamlet, Tanjung Pura District, Langkat Regency. This article uses descriptive research, which means a systematic, factual and accurate description of the facts, characteristics and relationships between the phenomena being investigated (Moleong, 2019). Research that uses a descriptive type is research that is intended to describe, depict, or explain the condition of the object being studied as it is, regarding how to develop children's Islamic talents and interests through Muharram celebration activities carried out by PGMI-3 UINSU students in community service activities carried out in Dahlia Hamlet. Tanjung Pura District, Langkat Regency. This research shows that starting from the urgency of interest in Islamic talents in children during Muharram Festival activities, namely recognizing interests and talents has many benefits in itself. The first benefit is that it makes it easier to determine the goals to be achieved. An important role in human life is played by interests and talents in all age groups which influence behavior and attitudes, this occurs especially in early childhood. Therefore, by recognizing and developing our interests and talents, we will easily achieve our desired goals. And for Muharram celebration activities, the Muharram celebration competition is divided into several categories, namely: call to prayer competition, short letter memorization competition, daily prayer memorization competition, calligraphy coloring competition, Islamic speech competition and also fashion show competition. And this Muharram Festival activity can become a vehicle for broadcasting Islamic religious values ​​in society.